Konstruksi citra partai Islam pada pemilu 2014 pendekatan fikih-siyasah - Iding Rosyidin; Gun Gun Heryanto (State Institute of Islamic Studies (IAIN) Salatiga, 2015)
The research of the Image Construction of Islamic Political Party at 2014 Election in Indonesia aimed at knowing the image construction of Islamic political party, especially at Republika and Sindo newspaper.The thoeries used in this research are fikih siyasat (the characteristic of muslim leader), social construction of mass media and hierarchy of influence by using discourse analysis as an analytical technique. The method of the research is qualitative. And the Informans as research subject are the jurnalist, redaction and management representative of both newspaper.The founds of research showed that the news characteristic of both newspaper were almost same. From the social cognition there werea difference. Republika strived to counter every news related to the image of Islamic political party and Sindo did not. From the social context, the background of this news was 2014 Election. And from hierarchy of influence perspective, the impact of media organization level was strong as shown in the power of the owner like Hary Tanoe in Sindo as a chairman of MNC Group. So, Sindo never produced news that contradicted to Hary or Hanura Party. The impact of ideological level also strong as we can seein the news of Republika which not only related to the profit, but also the benefit of Islamic Party.keyword: Construction; Image; Islamic party; Hierarchy of influence; Discourse analysis